Intermittent antegrade warm-blood versus cold-blood cardioplegia in children undergoing open heart surgery: a protocol for a randomised controlled study (Thermic-3). Issue 10 (14th October 2020) - Heys, Rachael; Stoica, Serban; Angelini, Gianni; Beringer, Richard; Evans, Rebecca; Ghorbel, Mohamed; Lansdowne, William; Parry, Andrew; Pieles, Guido; Reeves, Barnaby; Rogers, Chris; Saxena, Rohit; et al.
Abstract : Introduction: Surgical repair of congenital heart defects often requires the use of cardiopulmonary bypass (CPB) and cardioplegic arrest. Cardioplegia is used during cardiac surgery requiring CPB to keep the heart still and to reduce myocardial damage as a result of ischaemia–reperfusion injury. Cold cardioplegia is the prevalent method of myocardial protection in paediatric patients; however, warm cardioplegia is used as part of usual care throughout the UK in adults. We aim to provide evidence to support the use of warm versus cold blood cardioplegia on clinical and biochemical outcomes during and after paediatric congenital heart surgery. Methods and analysis: We are conducting a single-centre randomised controlled trial in paediatric patients undergoing operations requiring CPB and cardioplegic arrest at the Bristol Royal Hospital for Children. We will randomise participants in a 1:1 ratio to receive either 'cold-blood cardioplegia' or 'warm-blood cardioplegia'. The primary outcome will be the difference between groups with respect to Troponin T levels over the first 48 postoperative hours. Secondary outcomes will include measures of cardiac function; renal function; cerebral function; arrythmias during and postoperative hours; postoperative blood loss in the first 12 hours; vasoactive-inotrope score in the first 48 hours; intubation time; chest and wound infections; time from return from theatre until fit for discharge; length of postoperative hospital stay; all-cause mortality to 3 months postoperative; myocardial injury at the molecular and cellular level. Ethics and dissemination: This trial has been approved by the London – Central Research Ethics Committee. Findings will be disseminated to the academic community through peer-reviewed publications and presentation at national and international meetings. Patients will be informed of the results through patient organisations and newsletters to participants. Trial registration number: ISRCTN13467772; Pre-results .